AI-Based Teaching Using Bing Image Creator (AI Art Generator): Teaching English Writing a Descriptive Text Illustrated by 3D Animation Design Style - Tira Nur Fitria (International Journal of Computer and Information System (IJCIS), 2025)
Recently, posters or images with designs similar to Disney Pixar have been circulating on various social media platforms, such as Instagram and TikTok. With a design that is quite adorable, it is no wonder that the image design created using artificial intelligence (AI) has attracted the attention of people. Seeing the popularity of posters via Bing Image Creator, people can try to create character descriptions according to their favourite cartoons/ animations, such as Disney, via Bing Image Creator. This research simulated the use of Bing Image Creator to teach writing an English descriptive text to be illustrated into an animation or a cartoon. The analysis shows that the Bing Image Creator AI application is currently entertaining to create/produce the images they want without having design or drawing skills. This research is descriptive qualitative research. Teachers/lecturers can ask students to visit or access Bing Image Creator at https://www.bing.com/create. Students need to have a Microsoft account, but if they do not have one, they can create an account first. They sign in using a Microsoft account. After logging in, type the character description into the column provided. They can enter character descriptions as desired. To create a Disney AI cartoon, students can add the words "Disney Pixar style" to the beginning of the character description. They can create more specific commands to turn photos into Disney cartoons. The order may include descriptions such as 1) gender, male or female. 2) character shape, such as face shape, eyes, jaw, nose, cheeks, hair, clothes, position of body parts, and others. 2) certain poses/styles and accessories used. 3) objects worn on body parts, for example, types of clothing, colors, motifs/patterns. 4) objects used or around 5) expression, facial expression, or feeling. 6) activities carried out. 7) shooting angle. 8) surrounding background. To get accurate animated image results, students can write detailed and specific descriptions. Finally, wait for the image to finish and download it. Further research still needs to be carried out to determine students' perceptions of the use of Binh Image Creator in illustrating their written character descriptions of a desired cartoon. Keywords: AI-based teaching, Bing Image Creator, teaching writing, descriptive text,